-2z=-z+9

Simple and best practice solution for -2z=-z+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2z=-z+9 equation:


Simplifying
-2z = -1z + 9

Reorder the terms:
-2z = 9 + -1z

Solving
-2z = 9 + -1z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add 'z' to each side of the equation.
-2z + z = 9 + -1z + z

Combine like terms: -2z + z = -1z
-1z = 9 + -1z + z

Combine like terms: -1z + z = 0
-1z = 9 + 0
-1z = 9

Divide each side by '-1'.
z = -9

Simplifying
z = -9

See similar equations:

| -5(x-2)+8x=5x-6 | | 36+7n=6(n+7) | | 13=7+21t-16t^2 | | 10-4j-7=-9-7j | | 2x+6=3+6x-7 | | -7625+185t=0 | | 2q=18.92+6.3q | | 13.9j-9.71-8.7=9.43+16.3j | | -4y=-3y-10 | | 7x+4(x-5)=3(x+2)-5 | | 8x-3y=14fory | | 2x+5+6x-1=90 | | 3+10q=6+9q | | 3/4z=-5+1/2 | | 19.03+11.2y=5.1y-17.59-9.13 | | 4(-6x+1)=20-8x | | 335=5x^3 | | 8x+5-2x=-(5x-x) | | 3/4z=-5.5 | | 14.7t-5.79=15t | | 9h-(2h-4h+1)=38-2h | | 15.7g+18.66+7.2g=19.5g-13.64 | | -3(5a+6)=-5a+22 | | 0.7x-0.1=0.6x+2 | | 15x=2(1+9x) | | 2/3x=44 | | (5/9x)-(1/3)=3 | | -6r+1=-7r+20 | | 30+3x=-(3x+6) | | 3(x-4)=4x+1 | | -7-9k=7-7k | | =2z^2+13z+15 |

Equations solver categories